TREN PRODUK HALAL, GAYA HIDUP SYAR’I DAN KESALEHAN SIMBOLIK: STUDI TENTANG MUSLIM KELAS MENENGAH - Rina Darojatun (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2018)
Abstract: The appearance of muslim middle class In Indonesia present religious value in the middle of the fertie of consumerism in various field, especially in economy and education field. Trends of halal products and shar'i lifestyle are offered not only food and beverages, but health, beauty, tourism, transportation, financial institutions and Sharia property also complement the needs of Muslims to strengthen themselves had applied the tenet of Islam in order to get piety alive. The piety meant as symbolical of muslim obedience in attending Islamic sharia in various ascpect of life. This study aims to find out how the used of halal poducts and shar’i life style among muslim middle class will formed a symbolic piety that includes the meaning self concept and interaction with community. This study also used qualitative methods with phenomenology approach to capture the growing phenomenology in muslim middle class and symbolic interaction theory to analyze the symbol of piety attached to muslim interaction. The conclusion of this research is that muslims could formed and managed virtuous behavior with symbols and attributes attached to him by considering the expectation of others, although not fully implement the piety ritual according to Islamic shari’ah based on Al Qur’an and Hadish. Keywords: symbolic piety, phenomenology, symbolic interaction